An update on inflammatory breast cancer - P. Thapaliya; N. J. Karlin (Frontiers Media S.A., 2011)
Inflammatory breast cancer is one of the most aggressive forms of breast cancer. Once considered to be a uniformly fatal disease, treatment of this entity has evolved significantly over the last two decades. In this article, we review the epidemiology, pathology, biologic underpinnings, radiologic advances, and treatment modalities for inflammatory breast cancer. Updates in surgical therapy, medical oncologic therapy and radiation therapy are reviewed. Emphasis is on cutting edge information regarding inflammatory breast cancer. The management of inflammatory breast cancer is best served by a multidisciplinary team. Continued research into molecular pathways and potential targets is imperative. Future clinical trials should include evaluation of conventional therapy with targeted therapies.